Considerações sobre fala-leitura-escrita e efeitos clínicos no atendimento de afásicos - Guadagnoli, Carolina Fontes (2008)
Aphasic patients commonly present talking disturbances as a result of brain injury. In the speech therapy clinic, patients complaints usually involve difficulties related to talking. However, problems related to reading and writing can be quite surprising and demonstrate that the main issue of aphasic patients is related to the speech process. Reading and writing are, like talking, subjective activities and, as such, a rich area for therapeutic approaches. The objectives of this study are to (1) review the literature and comment on the different clinical presentations of aphasia in relation to talking, reading and writing; (2) present and discuss the effect of this context in the Speech Therapy Clinic; (3) compare these findings with the ones that the Research Group Aquisição, patologias e clínica de linguagem support (Group Coordinated by Prof. Maria Francisca Lier-De Vitto no LAEL/PUC-SP); (4) discuss clinical issues related to the implementation of activities that involve not only talking but also reading and writing. For this purpose, I present a report of four case studies. It is important to remark that many other researchers and scientists have also evidenced and described many interesting findings in this group of patients, and this was the motivation of this study. Nevertheless, reports are much more restricted to the observations of signs and clinical presentations, with little appraisal of the relation with reading and writing, other symptoms and therapeutic approaches. In conclusion, impasses and clinical handering of aphasic patients demand more discussion and attention in the literature